NN scattering: Chiral predictions for asymptotic observables - Ballot, J. L.; Robilotta, M. R.; Da Rocha, C. A. [UNESP] (American Physical Society (APS), 1998)
We assume that the nuclear potential for distances larger than 2.5 fm is given just by the exchanges of one and two pions and, for the latter, we adopt a model based on chiral symmetry and subthreshold pion-nucleon amplitudes, which contains no free parameters. The predictions produced by this model for nucleon-nucleon observables are calculated and shown to agree well with both experiment and those due to phenomenological potentials.